Perkembangan Terbaru dalam Paradigma Administrasi Publik: New Public Governance - Ali, Muhammad; Kabul, Lalu Muh. (Lembaga Yasin AlSys, 2025)
The research is motivated by the difference paradigms in public administrative science such as public administration paradigm of Nicholas Henry, Mark, and Osborne. The difference occurred due to there is no classification yet. The research aims to analyze latest development in revolutionary paradigm of public administration. A qualitative approach is employed, utilizing literature review with an integrative technique. Data is collected from various sources such as articles, books, and other text, and analized by content analysis. The result indicate that public administrative science can be classified into two paradigms, namely evolutionary paradigm and revolutionary paradigm. A public administration paradigm of Nicholas Henry can be classified into evolutionary paradigm. Meanwhile, a public administration paradigm of Mark and Osborne can be classified into revolutionary paradigm. In the context of revolutionary paradigm, latest development paradigm of public administration is new public governance.